1991
DOI: 10.1111/j.1365-2826.1991.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Relaxin Affects the Release of Luteinizing Hormone in Rats

Abstract: The effects of intravenous injection of porcine relaxin on the pulsatile secretion of luteinizing hormone (LH) were investigated in conscious rats. In untreated, ovariectomized animals, relaxin at doses 2.5 to 10 pglrat caused a dose-dependent suppression of pulsatile release of LH. At 5 y g relaxin, pulses were suppressed for approximately 60 rnin and there was a significant (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We have also shown that the dipsogenic actions of porcine relaxin in conscious rats require an intact brain angiotensin-11 system: central blockade with saralasin completely inhibits relaxin-induced drinking behavior (52). Finally, the action of relaxin on luteinizing hormone release in conscious rats is blocked by saralasin pre-treatment (60).…”
Section: Relaxin and The Forebrain Angiotensin-ll Systemmentioning
confidence: 95%
“…We have also shown that the dipsogenic actions of porcine relaxin in conscious rats require an intact brain angiotensin-11 system: central blockade with saralasin completely inhibits relaxin-induced drinking behavior (52). Finally, the action of relaxin on luteinizing hormone release in conscious rats is blocked by saralasin pre-treatment (60).…”
Section: Relaxin and The Forebrain Angiotensin-ll Systemmentioning
confidence: 95%
“…Measurements of relaxin in ovarian cycles and throughout pregnancy indicate, in agreement with histological studies, that the ovary and uterus produce relaxin in a manner that is dependent upon steroid hormone and/or gonadotrophin secretion, and that pituitary-ovarian-uterine feedback mechanisms may exist [48,54,55]. Because the corpus luteum and preplacental endometrium are important regulators of early implantation in natural conceptive cycles the functional regulation of relaxin secretion in these tissues will be discussed but will be limited to a summary of the effects of steroid hormones and gonadotrophins.…”
Section: Ovarian Relaxin Secretion and Functional Regulationmentioning
confidence: 64%
“…Relaxin has also been found to affect the hormones of the anterior pituitary gland, where it promotes prolactin secretion in rats and monkey [95], enhances secretion of growth hormone in monkeys [111], and inhibits release of luteinizing hormone in rats [112]. The presence of relaxin-3 and both LGR7 and GPCR135 in the nucleus incertus have led to speculation that relaxin-3 may have a role in regulating the level of behavioural activation, influencing attention, motivation, locomotion, and learning [86,92].…”
Section: Other Effects Of Relaxin Peptides In the Brainmentioning
confidence: 99%